2020
DOI: 10.3390/d12040157
|View full text |Cite
|
Sign up to set email alerts
|

A Common Approach to the Conservation of Threatened Island Vascular Plants: First Results in the Mediterranean Basin

Abstract: The Mediterranean islands represent a center of vascular plant diversity featuring a high rate of endemic richness. Such richness is highly threatened, however, with many plants facing the risk of extinction and in need of urgent protection measures. The CARE-MEDIFLORA project promoted the use of ex situ collections to experiment with in situ active actions for threatened plants. Based on common criteria, a priority list of target plant species was elaborated, and germplasm conservation, curation and storage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…Our study demonstrated that the conservation status of a plant globally considered endangered could notably vary at small spatial scale and suggested that conservation efforts must be supported by local analysis more than global investigation. Such evidence leads us to confirm that the priorities of conservation should vary at the small local level (Fenu et al 2020), since a population could need different conservation measures depending on the peculiar local conditions.…”
Section: Conservation Implicationssupporting
confidence: 53%
See 1 more Smart Citation
“…Our study demonstrated that the conservation status of a plant globally considered endangered could notably vary at small spatial scale and suggested that conservation efforts must be supported by local analysis more than global investigation. Such evidence leads us to confirm that the priorities of conservation should vary at the small local level (Fenu et al 2020), since a population could need different conservation measures depending on the peculiar local conditions.…”
Section: Conservation Implicationssupporting
confidence: 53%
“…Recent studies indicated that the conservation needs vary at the small local level in the Mediterranean territories since a plant species could need different conservation attentions depending on the particular conditions of the locality on which it grows (Fenu et al 2020), and thus, the local demographic trends should be the main guide to plan conservation measures at the restricted local scale. Consequently, the pivotal question is to know whether having data and general assessments on a threatened species are (or not) determinant to identify effective conservation measures for such species.…”
Section: Introductionmentioning
confidence: 99%
“…This approach may be pursued for endemic plants that require conservation efforts to prevent or mitigate the extinction risk. As recently demonstrated, the multiplication in nursery for several Mediterranean threatened endemic plants was an easy procedure, not cost-expensive and a practicable solution to obtain a large number of new individuals for several uses [16,256].…”
Section: Criticism and Future Perspectivesmentioning
confidence: 94%
“…Considering that a large number of medicinal and aromatic plants utilized all over the world are threatened [251] and two thirds of them are directly collected in the wild, it is necessary to promote and plan a rational exploitation of the plant biodiversity as a source of new bioactive substances. This observation is even more true for the endemic species, since they are particularly sensitive due to their restricted distribution and the small and often fragmented population size [15][16][17][252][253][254]. Thus, additional routes for resupply plant material need to be considered and, among the feasible strategies, the ex situ cultivation of threatened medicinal plants represents an encouraging protective approach in order to reconcile the conservation needs with research in the pharmaceutical field [19,255].…”
Section: Criticism and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation